2023
DOI: 10.3390/ijms241310584
|View full text |Cite
|
Sign up to set email alerts
|

Oyster Mushroom Spherical Virus Crosses the Species Barrier and Is Pathogenic to a New Host Pleurotus pulmonarius

Xiaoyan Zhang,
Haijing Hu,
Yanxiang Zhao
et al.

Abstract: Oyster mushroom spherical virus (OMSV) is a mycovirus with a positive-sense single-stranded RNA genome that infects the edible mushroom Pleurotus ostreatus. OMSV is horizontally transferred from an infected strain to a cured strain via mycelia. The infection results in significant inhibition of mycelial growth, malformation of fruiting bodies, and yield loss in oyster mushrooms. This study successfully transferred OMSV from P. ostreatus to Pleurotus pulmonarius. However, transmission was not successful in othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The Cryphonectria nitschkei chrysovirus 1 can be horizontally transmitted from its original host C. nitschkei to C. radicalis and C. naterciae strains [ 33 ]. A previous study conducted by the authors confirmed the horizontal transmission capability of the OMSV Chinese strain (OMSV-Ch) from P. ostreatus 8129 to P. pulmonarius strain XH2208 via mycelial contact [ 27 ]. In this study, OMSV-infected P. pulmonarius was co-cultured with other strains of Pleurotus species, revealing that OMSV could indeed spread horizontally from P. pulmonarius to P. floridanus .…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The Cryphonectria nitschkei chrysovirus 1 can be horizontally transmitted from its original host C. nitschkei to C. radicalis and C. naterciae strains [ 33 ]. A previous study conducted by the authors confirmed the horizontal transmission capability of the OMSV Chinese strain (OMSV-Ch) from P. ostreatus 8129 to P. pulmonarius strain XH2208 via mycelial contact [ 27 ]. In this study, OMSV-infected P. pulmonarius was co-cultured with other strains of Pleurotus species, revealing that OMSV could indeed spread horizontally from P. pulmonarius to P. floridanus .…”
Section: Discussionmentioning
confidence: 88%
“…A previous study demonstrated that OMSV could be horizontally transmitted via mycelia [ 27 ]. Two OMSV-infected strains, P. ostreatus strain 8129 and P. pulmonarius strain XH2208, were cultivated to investigate the possibility of vertical transmission through sexual basidiospores.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations